Analysis of Factors Influencing The Loyalty of Online Transportation Users in Indonesia - Fedianty Augustinah; Fitria Halim; Acai Sudirman; Onita Sari Sinaga (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The main objective of the research is to analyze the effect of e-service quality, price and consumer trust on the loyalty of online transportation users. The research method uses quantitative research. Based on the results of data analysis, e-service quality, price and consumer trust have a positive and significant effect on the loyalty of online transportation users. The implications of this research confirms that efforts to provide satisfactory user experience, fast and efficient service, good communication, qualified drivers, effective problem solving, and create a good reputation, online transportation platforms can strengthen user loyalty.